Changes in Skeletal Muscle Mass Assessed by Anthropometric Equations after Resistance Training - Gobbo, L. A.; Ritti-Dias, R. M.; Avelar, A.; Silva, A. M.; Coelho-e-Silva, M. J.; Cyrino, E. S. (International Journal of Sports Medicine, 2013)
The aim of this study was to analyze the validity of anthropometric equations to identify changes in skeletal muscle mass (SMM) after resistance training (RT). Anthropometric and dual energy x-ray absorptiometry (DXA) measurements were obtained at baseline and after RT in 15 trained Caucasian college men. Participants performed RT over 8 weeks, consisting of 8–9 exercises of 4 sets with 12/10/8/6 maximal repetitions and 1–2 min interval between sets. The training loads were gradually increased according to gains in muscular strength. 4 anthropometric equations were used for estimation of SMM: EQ1 (SMM, g=height×[0.0553×corrected thigh girth2  + 0.0987×forearm girth2 + 0.0331×corrected calf girth2] – 2445), EQ2 (SMM, g=height×[0.031×medial thigh girth2 + 0.064×corrected calf girth2 + 0.089×corrected arm girth2] – 3006), EQ3 (SMM, kg=height×[0.00744×corrected arm girth2 + 0.00088×corrected thigh girth2 + 0.00441×corrected calf girth2] + 2.4×gender – 0.048×age + race + 7.8) and EQ4 (SMM, kg=0.244×weight + 7.8×height + 6.6×gender – 0.098×age + race – 3.3). EQ1 and EQ2 overestimated the SMM (41.3% and 19.9%, respectively; P<0.05) while EQ3 and EQ4 were similar (P>0.05) to DXA at baseline. Although all equations and DXA revealed a significant increase in SMM after RT, changes were overestimated by EQ1 and EQ2 (P<0.05), but not by EQ3 and EQ4 (P>0.05). In addition, changes in SMM over time between EQ4 and DXA were significantly correlated (r=0.62; P<0.01). Thus, changes in SMM that occur after RT can be detected by EQ4 in trained young men.
Keywords: anthropometry; body composition; skinfold thickness; girths; weight exercises